Synthesis, 2D NMR, Electrochemistry and Luminescence Ruthenium(II) Complexes with 2,2'-Bipyridine and 5-(ω-Bromoalkylamido)-1,10-phenanthroline - Wang, Peng; Jing, Xiaoyan; Wang, Xiangping; Wang, Jun; Zhu, Guoyi (Asian Journal of Chemistry, 2010)
The efficient synthesis of 5-(5-bromovaleramido)-1, 10-phenan· throline, 5-(6-bromohexanamido)-1,10-phenanthroline, and 5-(11-bromoundecanamido)- 1,10-phenanthroline are described, which reacted with cis-Ru(bpy)2CI2·2H2O and sodium hexafluorophosphate to form Ru(bpy)2[phen-NHCO(CH2)nBr](PF6)2 (n = 4, 5 or 10; phen = 1,10- phenanthroline). The intricate 1H NMR spectra at low field of these complexes were completely assigned in virtue of 1H-1H COSY technique. Cyclic voltammetry was used to study electrochemical behaviours of these complexes, and their luminescent properties were investigated with fluorescent spectra.